A control method for hydraulic fracturing of the hard roof with long and short boreholes - Ma, Jinkui; Li, Hong; Guo, Xiaomin; Tian, Fuchao; Guo, Huaiguang (Frontiers in Materials, 2022)
During the mining of the working face, the hard roof can lead to a series of problems, such as air leakage in goafs, gas emission and concentration, casualties, and damages to buildings and ecological environment. The treatment of the hard roof has always been a difficult problem in major coal-producing countries. Although many scholars have conducted some theoretical research and field practice in this field in recent years, the aforementioned safety problems still occur frequently. In order to understand the mechanism of crack propagation caused by hydraulic fracturing of the roof, based on the theoretical analysis of linear elastic fracture mechanics and coal rock mechanics, the shear fracture criterion was determined for the formation of horizontal fractures in the natural cracks. The anisotropy of the crack tip, the adhesion forces in the coal and rock fracture surface and the conditions for hydraulic-induced crack propagation were also considered. The formation of cracks involves a vertical main crack and multiple extended-airfoil branch cracks which interconnect transversely and longitudinally. Under the effect of hydrodynamic water wetting and hydraulic fracturing, the stress of coal and mass changed. Meanwhile, the mechanical parameeters, such as compression, tensile strength and elasticity modulus and etc., were weakened, thus achieving the goal of structural transformation and slight weakening of coal and rock mass. According to the bidirectional stress of coal and rock mass, the maximum principal compressive stress of crack opening was calculated, and the propagation mechanism of hydraulic fracturing cracks in the hard roof was obtained. The hydraulic fracturing technology for controlling the hard roof was illustrated and has been applied in No. 2 Well of Sihe Coal Mine for many years. The research results could provide reference for the control of the hard roof in other similar mines.